2021
DOI: 10.1002/ejhf.2071
|View full text |Cite
|
Sign up to set email alerts
|

Advanced cancer is also a heart failure syndrome: a hypothesis

Abstract: We present the hypothesis that advanced stage cancer is also a heart failure syndrome. It can develop independently of or in addition to cardiotoxic effects of anti‐cancer therapies. This includes an increased risk of ventricular arrhythmias. We suggest the pathophysiologic link for these developments includes generalized muscle wasting (i.e. sarcopenia) due to tissue homeostasis changes leading to cardiac wasting associated cardiomyopathy. Cardiac wasting with thinning of the ventricular wall increases ventri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…We also hypothesize that the combination of these factors cause significant oxidative stress and tissue inflammation, leading to homeostasis changes in the heart with cardiac wasting, apoptosis, fibrosis and sympathetic nervous system activation, ultimately contributing to arrhythmia development in these patients. This could then lead to an excess mortality 27 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We also hypothesize that the combination of these factors cause significant oxidative stress and tissue inflammation, leading to homeostasis changes in the heart with cardiac wasting, apoptosis, fibrosis and sympathetic nervous system activation, ultimately contributing to arrhythmia development in these patients. This could then lead to an excess mortality 27 …”
Section: Discussionmentioning
confidence: 99%
“…In cancer mouse models, cardiac wasting was associated with impaired cardiomyocyte ultrastructure, fibrosis, reduced cardiac myocyte size, and fewer sarcomeric proteins 28,29 . Furthermore, autophagy was increased in the cardiac muscle wasting – whereas in skeletal muscle wasting the ubiquitin‐proteasome system was increased 27 . In a lung cancer mouse model examining the axons of the left ventricle, animals with cardiac wasting had 50% less dense core vesicles and 50% shorter axon 30 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A strong link between cancer and HF is shown by multiple data 21 . Anker et al 22 . suggested that advanced cancer may also be considered a HF syndrome.…”
Section: Oncologymentioning
confidence: 99%